(untitled) (Nigerian Journal of Physiological Sciences, 2023)
Pregnancy and lactation are normal physiological conditions that tend to influence numerous biological processes. The aim of this study was to identify the impact of pregnancy and lactation on serum vitamin D level and antioxidant status in some women in Zaria, Nigeria. A cross‑sectional descriptive study conducted at Ahmadu Bello University Teaching Hospital, Zaria for a period of three (3) months. Blood samples were collected, serum catalase, superoxide dismutase, lipid peroxidation and vitamin D, were determined using standard methods. Data were presented as mean ± SD, analysis was performed using one-way ANOVA and Pearson’s correlation analysis. Values were considered significant at p ≤ 0.05. There was a significant difference (p < 0.01) serum malondialdehyde level, superoxide dismutase activity and glutathione peroxidase activity during the various trimesters of pregnancy and lactating group. However, the levels of these markers were highest in the lactating group. Furthermore, serum level of vitamin D and catalase activity was highest in the 2nd trimester and lowest in the control and lactating group respectively. Pregnancy and lactation altered serum level of Vitamin D, CAT, SOD, MDA and GPx suggesting a variation in oxidative stress at different trimester of pregnancy and lactation. Key words: Pregnancy, lactation, oxidative stress, vitamin D